2001
DOI: 10.1046/j.1464-410x.2001.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematuria in Africa: is the pattern changing?

Abstract: Objective To study the aetiological factors and clinical presentation of haematuria as seen in a tertiary healthcare centre in a developing country in Africa. Patients and methods The study comprised a retrospective review of the diagnostic indices and notes of patients with macroscopic haematuria presenting at the Ahmadu Bello University Teaching Hospital, Zaria, Nigeria, over a 7‐year period from 1985 to 1991. Results Of a total of 2726 urology patients and 11 232 surgical patients, 482 had haematuria (17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Reports from the early 1990s suggested that simply asking about subjective gross hematuria could serve as a screen for urinary schistosomiasis with improvements in sensitivity by adding clinician observation and reagent strips [20,21]. Studies over time, all based on individual clinics or hospitals in Nigeria, have shown schistosomiasis has become an uncommon cause of gross hematuria in the country with the emergence of BPH and urologic malignancies [8,22,23]. A clinic series of 100 adult patients found BPH, trauma, infection, malignancy, and calculi to account for 90% of cases [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports from the early 1990s suggested that simply asking about subjective gross hematuria could serve as a screen for urinary schistosomiasis with improvements in sensitivity by adding clinician observation and reagent strips [20,21]. Studies over time, all based on individual clinics or hospitals in Nigeria, have shown schistosomiasis has become an uncommon cause of gross hematuria in the country with the emergence of BPH and urologic malignancies [8,22,23]. A clinic series of 100 adult patients found BPH, trauma, infection, malignancy, and calculi to account for 90% of cases [22].…”
Section: Discussionmentioning
confidence: 99%
“…A clinic series of 100 adult patients found BPH, trauma, infection, malignancy, and calculi to account for 90% of cases [22]. Hospital-based studies show roughly 30% of cases are due to BPH and 30% to urological malignancies [8,23]. Interesting disease-specific reports have demonstrated that over 40% of renal cell carcinomas present with the class triad of gross hematuria, flank pain, and a palpable mass and that the composition of urinary stones are moving toward that observed in industrialized countries [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for an educational programme to alert people to the significance of haematuria as an event requiring investigation and, of course, the ability to respond to this, should be a high priority. The development of mobile diagnostic services to outlying hospitals and health centres is proposed as an appropriate way to tackle the issue in Nigeria [6].…”
Section: Haematuriamentioning
confidence: 99%
“…Unfortunately, in older adults haematuria is not taken that seriously, so the diagnosis of bladder cancer may be delayed. The development or re‐development of haematuria in a person aged > 30 years should be investigated as carcinoma and not treated as a recurrence of bilharzia [5]. Consequently, bladder cancer (usually squamous cell carcinoma) is diagnosed late and is incurable by surgery or radiotherapy, the latter being available in only a few centres and not particularly effective.…”
Section: Urological Diseases In Sub‐saharan Africamentioning
confidence: 99%